2021
DOI: 10.1016/j.cmet.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infects human pancreatic β cells and elicits β cell impairment

Abstract: Emerging evidence points towards an intricate relationship between the pandemic of coronavirus disease 2019 (COVID-19) and diabetes. While pre-existing diabetes is associated with severe COVID-19 , it is unclear if COVID-19 severity is a cause or consequence of diabetes . To mechanistically link COVID-19 to diabetes, we tested whether insulin-producing pancreatic β-cells can be infected by SARS-CoV-2 and cause β-cell depletion. We found that the SARS-CoV-2 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
300
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(359 citation statements)
references
References 56 publications
9
300
1
7
Order By: Relevance
“…Angiotensin-converting enzyme 2 (ACE2) is found in the lungs, and pancreas serves as the entry receptor for COVID-19. The ACE2 protein allows entry of SARS-CoV-2 into pancreatic islet cells and may injure the beta cells [76,77]. Also, severe COVID-19 increases insulin resistance through enhanced secretion of stress hormones (cortisol and others) and cytokines [78].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2) is found in the lungs, and pancreas serves as the entry receptor for COVID-19. The ACE2 protein allows entry of SARS-CoV-2 into pancreatic islet cells and may injure the beta cells [76,77]. Also, severe COVID-19 increases insulin resistance through enhanced secretion of stress hormones (cortisol and others) and cytokines [78].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Some reports show no expression of ACE2 in the islets of Langerhans but in pancreatic epithelial cells only, 24 , 25 , 26 whereas other studies in patients without COVID-19 have shown expression of ACE2 in β cells. 27 , 28 , 29 A sub-group of authors of this Review previously investigated expression of ACE2 and SARS-CoV-2 infection of β cells in 11 patients who died due to COVID-19. 30 Compared with other study cohorts of just one to three patients, we observed that only around 30% of the patients expressed ACE2 in β cells, indicating that other factors were also involved in the infection.…”
Section: Metabolic and Endocrine Pathways Linked To Sars-cov-2mentioning
confidence: 99%
“…Additional factors expressed in pancreatic β cells have been identified as crucial for infection with SARS-CoV-2 ( figure 1 B). 29 , 30 NRP1, known to bind furin-cleaved substrates, facilitates SARS-CoV-2 entry and infectivity, 60 suggesting that virus entry is increased in cells with a low expression of ACE2 due to promotion of the interaction between SARS-CoV-2 and ACE2 via NRP1. In addition, HMGB1, a DNA-binding protein that regulates chromatin and is known to be proviral, was shown to regulate the expression of ACE2 and be essential for viral entry.…”
Section: Metabolic and Endocrine Pathways Linked To Sars-cov-2mentioning
confidence: 99%
“…Two further studies also confirmed infection of β-cells in autopsy samples from people who died of COVID-19 and showed that COVID-19 infection leads to reduced production and release of insulin from pancreatic islet tissue. In particular, they showed that SARS-CoV-2 infection leads to the death of some of those all-important β-cells and causes transdifferentiation of the surviving cells ( 61 , 62 ). In addition, several studies in mice support the hypothesis that ACE2 is important in β cell homeostasis.…”
Section: Glucose Metabolismmentioning
confidence: 99%